2017
DOI: 10.1371/journal.pone.0169335
|View full text |Cite
|
Sign up to set email alerts
|

The Natural Flavonoid Fisetin Inhibits Cellular Proliferation of Hepatic, Colorectal, and Pancreatic Cancer Cells through Modulation of Multiple Signaling Pathways

Abstract: Digestive cancers are major causes of mortality and morbidity worldwide. Fisetin, a naturally occurring flavonoid, has been previously shown anti-proliferative, anti-cancer, neuroprotective, and antioxidant activities. In our study, the anti-tumor activities in addition to regulatory effects of fisetin on some cancer cell lines were investigated. Data presented here showed that fisetin induces growth inhibition, and apoptosis in hepatic (HepG-2), colorectal (Caco-2) and pancreatic (Suit-2) cancer cell lines. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(48 citation statements)
references
References 65 publications
2
45
0
1
Order By: Relevance
“…Moreover, it was reported that fisetin stimulated Nrf2 signalling, ERK/MAPK signalling, and kinases involved in cell cycle regulation in vitro [44]. Of interest, flavonoids were shown to influence various cyclin-dependent kinases [45], mitogen-activated protein kinases (MAPK), protein kinase Akt, and FoxO signalling [46] and to counteract inflammation [47-49].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it was reported that fisetin stimulated Nrf2 signalling, ERK/MAPK signalling, and kinases involved in cell cycle regulation in vitro [44]. Of interest, flavonoids were shown to influence various cyclin-dependent kinases [45], mitogen-activated protein kinases (MAPK), protein kinase Akt, and FoxO signalling [46] and to counteract inflammation [47-49].…”
Section: Resultsmentioning
confidence: 99%
“…13) Excessive evidence has demonstrated that fisetin could inhibit various chronic inflammation-related conditions, cell proliferation, oxidative stress, and cardiac hypertrophy. [14][15][16][17] Meanwhile, fisetin significantly attenuates the ischemia/reperfusion (I/R)-induced myocardial tissue injury by suppressing mitochondrial oxidative stress, and FISETIN REDUCES ATRIAL FIBRILLATION VULNERABILITY Table I. Information of Primers for RT-PCR…”
mentioning
confidence: 99%
“…However, poor bioavailability, rapid metabolization due to lipophilic, and highly insoluble nature, being effective in high doses, are among the major problems encountered by using curcumin clinically . Flavonoids are other well‐known and well‐studied natural product modulators that include flavonols, flavones, isoflavones, flavanols, flavanolols, flavanones, and chalcones . In addition to the fact that these compounds are modulators of ABC drug transporters, it is reported that they also alter the overall pharmacokinetics, including drug absorption, penetration, and elimination .…”
Section: Novel Strategies Against Mdrmentioning
confidence: 99%
“…97 Flavonoids are other well-known and well-studied natural product modulators that include flavonols, flavones, isoflavones, flavanols, flavanolols, flavanones, and chalcones. 98 In addition to the fact that these compounds are modulators of ABC drug transporters, it is reported that they also alter the overall pharmacokinetics, including drug absorption, penetration, and elimination. 99 Therefore, it is not surprising that the result of such interaction is not only the inhibition of transporters; some flavonoids can stimulate (rather than inhibit) ABC transporters, depending on the substrate of interest.…”
Section: Natural Products and Derivatives As Modulators To Reverse Mdrmentioning
confidence: 99%